Concurrent multiple intracranial and intramedullary tuberculoma: a rare form of neurotuberculosis - Tanwar, Vikram Singh; Singh, Harpreet; Govil, Nikhil; Arora, Sameer; Jagota, Ruchi (Journal of Advances in Internal Medicine, 2015)
Central nervous system tuberculosis is a serious form of tuberculosis. Tuberculous CNS involvement can occur in the form of TB meningitis, tuberculous Vasculitis, tuberculoma and rarely brain abscess. Tubercular granulomas generally solitary and occurs in the brain but it may be multiple and involve other areas such as spinal cord, epidural space and subdural space also. Tuberculoma in the spinal cord is rare. Concurrent occurrence of brain tuberculomas along with intramedullary spinal tuberculoma is even rarer. Only few cases have been reported in world literature. We are reporting a 28 years old female who presented with headache and progressive paraparesis in which imaging revealed intracranial and intramedullary tuberculoma and recovered completely with antitubercular therapy without any surgical intervention. Journal of Advances in Internal Medicine 2015;04(01):25-27